Adaptive Behaviors to Marine Ecosystem Shifts: Examining Fishermen’s Strategies in Response to Abundant Juvenile Sablefish (Anoplopoma fimbria) in Alaska - Szymkowiak, Marysia; Rhodes-Reese, Melissa (Frontiers in Marine Science, 2020)
Over recent years there have been rapid changes occurring across marine ecosystems worldwide, with high latitude systems seeing ecosystem shifts emerging at unprecedented rates. The Gulf of Alaska and Bering Sea marine ecosystems have experienced substantial fluctuation in fish stocks, with some species experiencing considerable decreases while others thrive. Following the marine heatwave of 2014, sablefish (Anoplopoma fimbria) had a historically unparalleled juvenile recruitment class that is now dominating the stock composition. While this recruitment class bodes well for future fisheries, it is currently undermining the value of the fishery with limited incentives to retain the smaller and less valuable fish, compounding adverse effects on earnings in the fishery due to whale depredation that has been occurring for years. This study examines the well-being implications of fishermen’s adaptive strategies to these ecosystem conditions within the Alaska sablefish fishery using a socio-ecological system framework, operationalized as a qualitative network model (QNMs) and quantitative indicators. We examine the extent to which adaptation strategies, derived from a literature review and stakeholder interviews, are being utilized in the fishery with quantitative indicators. These strategies are then examined with QNMs that explore their impacts across the spectrum of well-being. By coupling quantitative indicators and QNMs, we were able to demonstrate how adaptive strategies can be examined to capture the multi-faceted well-being effects of fisheries participants’ adaptations to changing conditions. This study directly addresses several of the key guiding principles of the U.S. EBFM Road Map, including advancing our understanding of ecosystem processes, exploring trade-offs within an ecosystem, and maintaining resilient ecosystems, inclusive of community well-being. Thus this paper demonstrates how coupled socio-ecological models can elevate the inclusion of human adaptive behaviors, providing a framework for the development of policymaking that can mitigate adverse effects on both the participants and the resource by facilitating the mixture of adaptive strategies that maximizes desired well-being outcomes.